2014
DOI: 10.5455/msm.2014.26.182-185
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-sectional Study of Midwives' Perspectives Towards their Professional Educational Needs

Abstract: Background:Midwives are one of the most important health care providers and meeting their professional educational needs can be effective in maternal and child health promotion.Aim:The aim of this study was to investigate the midwives’ perspectives towards their educational needs.Methods:In this cross-sectional study which was conducted in 2012 in Sari, North of Iran, 223 midwives during a convenience sampling method expressed their educational needs. The instrument of the data collection was a self-administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Midwives, as well as midwifery students, need training and education to develop in their profession. 35 To have early exposure to hands-on experience in clinical midwifery practice and woman-centred care provides students the opportunity to link theory into practice. 36,37 In the discussions participants made clear that being a good midwife and developing professionalism meant training, but also taking part in evidence-based research.…”
Section: Discussionmentioning
confidence: 99%
“…Midwives, as well as midwifery students, need training and education to develop in their profession. 35 To have early exposure to hands-on experience in clinical midwifery practice and woman-centred care provides students the opportunity to link theory into practice. 36,37 In the discussions participants made clear that being a good midwife and developing professionalism meant training, but also taking part in evidence-based research.…”
Section: Discussionmentioning
confidence: 99%
“…Since in Iran’s education system, there is no independent subject titled nursing ethics and observing patient’s rights in the nursing students’ curriculum, it is recommended that the curriculum be revised, and in-service educational courses be considered for nurses. In this respect, it has been shown that the need for education of observing professional ethics and regulations is among the needs of health care providers in continuous educational programs ( Abedian, Yazdani Charati, Samadaee, & Shahhosseini, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…And their new level of responsibility inspires the importance of continuous professional education in order to continue to provide safe care for women. Continuing education programs will help healthcare providers improve their professional competence and adapt them to rapidly changing and new roles (34)(35)(36). Particularly, midwives are one of the important healthcare providers, and their continuing education can enhance midwives' ability to improve maternal and child health status (37).…”
Section: Discussionmentioning
confidence: 99%